Configuration and Inverse Position Solution Analysis of a Novel（（2-RPR&RP）+R） &UPR Parallel Mechanism - Hu Weiwei; Mei Ying; Wang Shusen; Huang Faqun (Jixie chuandong)
A novel large swing angle 1T2R parallel mechanism is proposed. First,the one-dimensional translational and two-dimensional rotation motion of this mechanism are analyzed based on the relation of motion and constraint in screw theory. The DOF of the mechanism is calculated,and the driving joints are chosen.Then,the inverse position solution equation of the mechanism is established by using analytical vector method and the geometric relation. At last,the position inverse solution is obtained by using MATLAB and the results simulation verification is carried out by using ADAMS,which verify that the correctness of the inverse position solution model and the realizability of the mechanism. This parallel mechanism with a large swing angle,can be used in hybrid machine of parallel modules to achieve large swing angle five-axis machining.